Ketahanan Pangan Indonesia Memperkuat Wujud Nasionalisme - Taufiqurokhman Taufiqurokhman; Andriansyah Andriansyah (PETANDA: Jurnal Ilmu Komunikasi dan Humaniora, 2020)
The purpose of this research is to look at food security policies in realizing the ethos of nationalism, namely the fulfillment of household food with good, safe and equitable quality standards. The problem in writing this research is that food security is seen from various sides, economic, social and political, so that food security should not cause an instability in Indonesia. The research methodology uses qualitative descriptive analysis approach, with a desaint of research using Creswell's theory, J. W. (2014). Primary data in this study were obtained from the Ministry of Agriculture officials, for secondary data obtained from literature studies and documents relating to Food Security. The results of the study stated, (1) The agricultural sector is the main pillar of the development of almost all economic activities centered on the agricultural sector. (2) The government is obliged to guarantee the adequacy of food with good quality, price stability, for the community, especially for low income groups. (3) The archipelago's food security policy with the agricultural sector mentions the need for archipelago-minded agricultural centers that can streamline agricultural production so that the results can be maximized.